2018
DOI: 10.1002/pld3.56
|View full text |Cite
|
Sign up to set email alerts
|

Waterlogging affects plant morphology and the expression of key genes in tef (Eragrostis tef)

Abstract: Tef [Eragrostis tef (Zucc.) Trotter], an allotetraploid cereal that is a staple food to over 60 million people in the Horn of Africa, has a high nutritional content and is resistant to many biotic and abiotic stresses such as waterlogging and drought. Three tef genotypes, Alba, Tsedey, and Quncho, were subjected to waterlogging conditions and their growth, physiology, and change in transcript expression were measured with the goal of identifying targets for breeding cultivars with improved waterlogging toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 112 publications
2
13
0
Order By: Relevance
“…In addition, other genes involved in sucrose and starch metabolism and glycolysis were up-regulated in Yerong and Deder2 roots, such as α-amylase, SPS, phosphofructokinase and fructose-bisphosphate aldolase, NADP-GADH, and PK. These results were in agreement with recent studies in tef, a cereal grass [77], and maize [45].…”
Section: Effects On Carbon Metabolismsupporting
confidence: 94%
“…In addition, other genes involved in sucrose and starch metabolism and glycolysis were up-regulated in Yerong and Deder2 roots, such as α-amylase, SPS, phosphofructokinase and fructose-bisphosphate aldolase, NADP-GADH, and PK. These results were in agreement with recent studies in tef, a cereal grass [77], and maize [45].…”
Section: Effects On Carbon Metabolismsupporting
confidence: 94%
“…Such differential responses to waterlogging were also exhibited in the formation of aerenchyma in the roots. While Tsedey formed more aerenchyma than Alba and had accelerated growth under waterlogging, Tsedey and Quncho had constitutive aerenchyma (Cannarozzi et al 2018b).…”
Section: Physiology and Agronomymentioning
confidence: 95%
“…Since tef is resilient to extreme environmental conditions, differentially regulated genes were investigated under drought and waterlogging conditions. A recent study showed that under excess moisture, genes affecting carbohydrate metabolism, cell growth, response to reactive oxygen species, transport, signaling, and stress responses were differentially regulated (Cannarozzi et al 2018b).…”
Section: Omics Studies On Tefmentioning
confidence: 99%
See 1 more Smart Citation
“…In proso millet, RNA-seq data was first reported by Yue et al [193], which served as an excellent sequence resource for gene discovery and marker development in this crop. Few reports also available in other millets, including barnyard millet for drought tolerance, and Fe and Zn accumulation [77], submergence tolerance [120]; and in teff for waterlogging [24], to understand the gene regulatory mechanisms in these crops. These studies underline the application of transcriptomics in identifying the gene repertoire underlying the traits-of-study, which can then be further characterized and used in crop improvement.…”
Section: Transcriptomicsmentioning
confidence: 99%